(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A sensitive and selective liquid chromatography-mass spectrometry (LC-MS/MS) method using multiple reaction monitoring (MRM) mode was developed and validated for trace analysis of 4-(chloromethyl)-1, 2-dimethoxybenzene (Veratryl chloride) a potential genotoxic impurity in Ivabradine hydrochloride (IVB). Chromatographic separation was performed on a Poroshell 120EC C18 (50 × 3.0 mm, 2.7 μm) column using a mixture of 10 mM ammonium formate and acetonitrile in isocratic elution mode at a 0.25 mL/min flow rate. A simple pre-column derivatization with di-ethylamine was employed for the derivatization of the veratryl chloride. The developed LC-MS/MS method was linear and accurate in the 1.5–10.0 ppm concentration range with r2 ˃ 0.999 and percent recoveries greater than 90%. The developed method was precise with RSD (%) of not more than 4.5%. In-silico genotoxicity and carcinogenicity potential of veratryl chloride was assessed using ICH M7 principles found to be positive. The developed method can identify and quantify veratryl chloride in IVB, hence can be applied by quality control labs of pharmaceutical industries for trace quantification.